Inhibitory Control in Young Healthy Adults - a tDCS Study - Laskov, O; Biačková, Nina; Stuchlíková, Zuzana; Kostýlková, Lenka; Klírová, Monika (Physiological research, 2023)
Inhibitory control plays a role in the behavior selection and detection of conflicts. Defects in inhibitory control are an integral part of many neuropsychiatric disorders and the possibilities of influencing it are the subject of active study. Studies have shown and confirmed the activation of the dorsolateral prefrontal cortex (DLPFC) during the Stroop task and other tests involving response inhibition. Non-invasive brain stimulation is an emerging and actively developing group of methods used in cognitive research. In the present study, we used non-invasive, painless, and delicate transcranial direct stimulation (tDCS) for the study of inhibitory control, and to explore the effect of impulsivity on response inhibition ability in young healthy participants. We conducted a cross-over study with cross-hemispheric application of 2 mA tDCS with electrodes placed on the right - cathode, and left - anode - DLPFC. Participants performed a classic Stroop test before and after stimulation. Impulsivity was measured via the personal impulsiveness questionnaire. There was no significant difference in interference score alteration between active and sham stimulations, anodal and sham tDCS both induced slight improvement in Stroop test results. Individual impulsivity in healthy participants showed no influence on their results. Our study adds to the picture and helps to deepen knowledge about the impact of different stimulation parameters on cognitive functions.
Keywords: Prefrontal Cortex; zdraví dobrovolníci pro lékařské studie; Transcranial Direct Current Stimulation; přímá transkraniální stimulace mozku; prefrontální mozková kůra; Adult; Cross-Over Studies; kognice; dospělí; lidé; Healthy Volunteers; Humans; Cognition; klinické křížové studie